The correlation of the dynamic maximum strength of the standing calf raise with the sprinting performance between 5 and 30 metres - Möck, S.; Hartmann, R.; Wirth, K.; Rosenkranz, G.; Mickel, C. (Journal of Australian Strength and Conditioning, 2019)
Maximum strength of the plantar flexors correlates significantly (r = -0.460 to -0.675) with sprinting performance over short distances. Variations of the calf raise with extended knee should therefore be considered when designing resistance training programs for sprinting.